Individual behavior and housing setup interact to influence markers of welfare in the critically endangered Hawaiian crow - Rachel P. Gosselin; Alison M. Flanagan; Michael Mendl; Katelynn Earnest; Bryce Masuda; Alison L. Greggor (Applied Animal Behaviour Science, 2025)

An enclosure quality ranking framework for terrestrial animals in captivity - Alison M. Flanagan; Bryce Masuda; Koa Grabar; Lisa P. Barrett; Ronald R. Swaisgood (Applied Animal Behaviour Science, 2024)

What do animals learn during anti-predator training? Testing for predator-specific learning in ‘alalā (Corvus hawaiiensis) - Alison L. Greggor; Bryce Masuda; Anne C. Sabol; Ronald R. Swaisgood (Behavioral Ecology and Sociobiology, 2022)

Testing the maintenance of natural responses to survival-relevant calls in the conservation breeding population of a critically endangered corvid (Corvus hawaiiensis) - Anne C. Sabol; Alison L. Greggor; Bryce Masuda; Ronald R. Swaisgood (Behavioral Ecology and Sociobiology, 2022)

Genetic structure and population history in two critically endangered Kaua‘i honeycreepers - Loren Cassin-Sackett; Michael G. Campana; Nancy Rotzel McInerney; Haw Chuan Lim; Natalia A. S. Przelomska; Bryce Masuda; R. Terry Chesser; Eben H. Paxton; Jeffrey T. Foster; Lisa H. Crampton; Robert C. Fleischer (Conservation Genetics, 2021)

Moving from trends to benchmarks by using regression tree analysis to find inbreeding thresholds in a critically endangered bird - Alison M. Flanagan; Bryce Masuda; Catherine E. Grueber; Jolene T. Sutton (Conservation Biology, 2021)
Understanding how inbreeding affects endangered species in conservation breeding programs is essential for their recovery. The Hawaiian Crow (‘Alalā) ( Corvus hawaiiensis ) is one of the world's most endangered birds. It went extinct in the wild in 2002, and, until recent release efforts starting in 2016, nearly all of the population remained under human care for conservation breeding. Using pedigree inbreeding coefficients ( F ), we evaluated the effects of inbreeding on Hawaiian Crow offspring survival and reproductive success. We used regression tree analysis to identify the level of inbreeding (i.e., inbreeding threshold) that explains a substantial decrease in ‘Alalā offspring survival to recruitment. Similar to a previous study of inbreeding in ‘Alalā, we found that inbreeding had a negative impact on offspring survival but that parental (vs. artificial) egg incubation improved offspring survival to recruitment. Furthermore, we found that inbreeding did not substantially affect offspring reproductive success, based on the assumption that offspring that survive to adulthood breed with distantly related mates. Our novel application of regression tree analysis showed that offspring with inbreeding levels exceeding F = 0.098 were 69% less likely to survive to recruitment than more outbred offspring, providing a specific threshold value for ongoing population management. Our results emphasize the importance of assessing inbreeding depression across all life history stages, confirm the importance of prioritizing parental over artificial egg incubation in avian conservation breeding programs, and demonstrate the utility of regression tree analysis as a tool for identifying inbreeding thresholds, if present, in any pedigree‐managed population.

The influence of captive breeding management on founder representation and inbreeding in the ‘Alalā, the Hawaiian crow - Philip W. Hedrick; Paquita E. A. Hoeck; Robert C. Fleischer; Susan Farabaugh; Bryce M. Masuda (Conservation Genetics, 2016)